mathcal Synchronization for Fuzzy Markov Jump Chaotic Systems With Piecewise-Constant Transition Probabilities Subject to PDT Switching Rule - Wang, Jing; Xia, Jianwei; Shen, Hao; Xing, Mengping; Park, Ju H. (IEEE transactions on fuzzy systems, 2021)
This article investigates the nonfragile \mathcal {H}_{∞ } synchronization issue for a class of discrete-time Takagi-Sugeno (T-S) fuzzy Markov jump systems. With regard to the T-S fuzzy model, a novel processing method based on the matrix transformation is introduced to deal with the double summation inequality containing fuzzy weighting functions, which may be beneficial to obtain conditions with less conservatism. In view of the fact that the uncertainties may occur randomly in the execution of the actuator, a nonfragile controller design scheme is presented by virtue of the Bernoulli distributed white sequence. The main novelty of this article lies in that the transition probabilities of the Markov chain are considered to be piecewise time-varying, and whose variation characteristics are described by the persistent dwell-time switching regularity. Then, based on the Lyapunov stability theory, it is concluded that the resulting synchronization error system is mean-square exponentially stable with a prescribed \mathcal {H}_{∞ } performance in the presence of actuator gain variations. Finally, an illustrative example about Lorenz chaotic systems is provided to show the effectiveness of the established results.